Teaching the Big Concept of Chemistry in the Context of China's Basic Education Reform - Tang, Yanyan; Xu, Suyi; Xu, Ying; Wang, Pengyun (Advances in Social Sciences Research Journal, 2023)
In the eighth curriculum reform, China proposed to develop students' core literacy in disciplines, aiming to explore what kind of teaching mode and means can cultivate outstanding talents through Chinese school education, and emphasize the emphasis on the teaching of major concepts of disciplines to make the curriculum content structured. The teaching of major concepts is highly abstract and generalized, which can help students establish a knowledge structure system and promote the transfer and application of knowledge. This paper takes the knowledge of galvanic batteries as the carrier and the question of "why can the fan rotate" as the driving force, forms a cognitive model, and puts forward a unit teaching led by a large concept from the perspective of energy conversion, so that students can better understand the galvanic battery model and apply it to life, so as to promote the development of students' core literacy.